Kebijakan Pemerintah dalam Optimalisasi Pelayanan Publik: Studi Kasus pada Mini Mall di Desa Anggaswangi Kecamatan Sukodono Kabupaten Sidoarjo - Arliansyah, Ilham Yafie (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
The presence of a Public Service Mini Mall in Anggaswangi Village, Sukodono District, Sidoarjo Regency. The purpose of this research is to know the actual and factual study of Government Policy in Mini Mall Services in Anggaswangi Village, Sukodono District, Sidoarjo Regency and to find out the supporting and inhibiting factors of Government Policy in Optimizing Services at Mini Malls in Anggaswangi Village, Sukodono District, Sidoarjo Regency. This research method uses a qualitative case study method with one variable, namely, Government Policy in Optimizing Public Services (Case Study on Public Service Mini Mall in Anggaswangi Village, Sukodono District, Sidoarjo Regency), it is influenced by 5 factors including, public policy always has a spesific goal. Public policies contain government actions, public policies are what the government is still doing, public policies taken are positive, public policies are based on statutory regulations that are binding and coercive. Supporting factors for optimizing public services at Mini Malls in Anggaswangi Village, Sukodono Subdistrict, Sidoarjo Regency. Coordination of Sukodono Subdistrict as the person in Charge of Optimizing Public Services in Mini Mall Public Services, Technological Advances. Meanwhile, the inhibiting factors for optimizing public services at the Mini Mall in Anggaswangi Village, Sukodono District, Sidoarjo Regency, are the limited service time during the COVID-19 pandemic, and the limited time for making e-KTP forms.